(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Understanding the factors influencing loan repayment is essential for ensuring borrowers make timely loan payments. The microfinance model allows borrowers to access small business loans safely, aligned with ethical lending standards. Moreover, repayment behaviour highlights how individuals manage their debt, whether through on-time payments, paying more than the minimum, or defaulting. Objectives: This paper examines the factors influencing loan repayment among microfinance customers in Pokhara. Client, business, lender, and group characteristics are potential influencers of loan repayment. Methods: The study is based on a survey method with a purposive sampling technique, focusing on 120 respondents from registered microfinance institutions in Pokhara. Data was gathered using structured questionnaires, and the analysis was conducted using descriptive and inferential statistics. Results: The findings reveal that client characteristics such as age, marital status, and education significantly affect loan repayment, with middle-aged, married individuals showing better repayment behaviours. Business characteristics positively influence repayment, including enterprise type, years in operation, and business size. Lender characteristics such as MFI policies, monitoring, and performance are crucial in enhancing repayment, while group characteristics like peer support and pressure do not significantly impact repayment behaviour. Conclusion: The age, education, business type, and size of a client play a significant role, while lender policies and monitoring are also crucial. In contrast, group dynamics have less impact. Thus, microfinance institutions may focus on developing tailored financial products, flexible repayment schedules, and supportive programs to help clients repay their loans effectively. Keywords: Business characteristics, client characteristics, lender characteristics, loan repayment, microfinance institutions Paper Type: Research Paper JEL Classification: E4, E5, G21, G28